2021
DOI: 10.3390/infrastructures6060086
|View full text |Cite
|
Sign up to set email alerts
|

Cement-Bonded Particleboards with Banana Pseudostem Waste: Physical Performance and Bio-Susceptibility

Abstract: This article evaluates the relevant properties of cement-bonded particleboards (CBPB) made with a portion of maritime pine (Pinus pinaster) particles replaced with an agricultural waste, banana pseudostem (Musa sp.). The industrial production of CBPB was simulated in the laboratory based on a reference composition defined by a manufacturing company. Test specimens were produced assuming 0%, 25%, 50% and 75% partial replacement of wood particles with banana pseudostem fibres. Some physical properties (bulk dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Infrastructures 2022, 7, x. https://doi.org/10.3390/xxxxx www.mdpi.com/journal/infrastru that, in earth-straw composites, the shorter are the pieces of straw, the higher compressive strength. Future studies could deepen the influence of grain size o properties of boards since it can affect physical and mechanical properties [17,18 influence of sieving time on the results of the grain size analysis of bio-aggregates be further investigated, too. The test could be carried out considering several si times, evaluating the differences in the results and defining which guarantees the sm deviation in the grains size distribution, as Martínez-García et al [57] reported.…”
Section: Particle Size Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Infrastructures 2022, 7, x. https://doi.org/10.3390/xxxxx www.mdpi.com/journal/infrastru that, in earth-straw composites, the shorter are the pieces of straw, the higher compressive strength. Future studies could deepen the influence of grain size o properties of boards since it can affect physical and mechanical properties [17,18 influence of sieving time on the results of the grain size analysis of bio-aggregates be further investigated, too. The test could be carried out considering several si times, evaluating the differences in the results and defining which guarantees the sm deviation in the grains size distribution, as Martínez-García et al [57] reported.…”
Section: Particle Size Analysismentioning
confidence: 99%
“…This guarantees a more sustainable practice since the bio-wastes can be used directly as they are as by-products. The shredding may be necessary in case of compressed panels' production for which a finer grain size might be more adequate [17].…”
Section: Loose Bulk Density and Thermal Conductivitymentioning
confidence: 99%
See 2 more Smart Citations